The Official Languages Act and the English-speaking Community of Quebec : Looking to the Future - Johnston, Nicola (2010)
Remarks to the Standing Committee on Official Languages

The Official Languages Act and the English-speaking Community of Quebec : Learning from the Past - Donnelly, Robert (2010)
Keywords: Official Language Minority Community (OLMC)

Roadmap to Canada's Linguistic Duality 2008-2013 - Donnelly, Robert (2010)
Remarks to the Standing Committee on Official Language
Keywords: Official Language Minority Community (OLMC)

QCGN Opening Remarks to Committee on Culture and Education : General consultation and public hearings on Bill 14: An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Quebec Community Groups Network (QCGN) (2013)

Presentation to the Committee on Culture and Education on Bill 86 - Duszara, Walter; Chambers, Geoffrey; Maldoff, Eric; Martin-Laforge, Sylvia (2017)

Opening Remarks of Marlene Jennings, President of QCGN, to QCGN Hearings on Bill 96 - Jennings, Marlene (2021)

Opening Remarks by QCGN President, the Honourable Marlene Jennings, P.C., LLB to the Committee on Culture and Education : Special Consultations and Public Hearings on Bill 96, an Act Respecting French, the Official and Common Language of Quebec - Jennings, Marlene (2021)

Mot d’ouverture de Marlene Jennings, présidente du QCGN, lors des audiences publiques du QCGN sur le projet de loi no 96 - Jennings, Marlene (2021)

Linda Leith Remarks to OCOL Part VII Forum - Leith, Linda (2011)
Keywords: Official Language Minority Community (OLMC)

Discours d’ouverture de la présidente du QCGN, l’honorable Marlene Jennings, C.P., LL. B. au Commission de la culture et de l'éducation : Consultations particulières et audiences publiques sur le projet de loi 96, Loi sur la langue officielle et commune du Québec, le français - Quebec Community Groups Network (QCGN) (2021)

Closing Remarks of Kevin Shaar, Vice-President of QCGN, to QCGN Hearings on Bill 96 - Shaar, Kevin (2021)